Тенденції динаміки енергоємності виробництва аміаку в Україні та перспективи її зниження - Bogomolets T.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2004)
The computations of power capacity and full power capacity ammonia production at 1995-2000 and up to 2015 are given.